Camel milk Lactococcus lactis subsp. cremoris: a biocontrol agent against Staphylococcus aureus for fresh beef biopreservation - Latreche, Bilal; Brahamia, Nabila; Bendjama, Esma; Loucif, Lotfi; Sanah, Ibtissem; Djeghim, Fairouz; Messaoudi, Mohammed; Giordano, Irene; Rolain, Jean-Marc; D’Elia, Maria; Rastrelli, Luca; Becila, Samira (Frontiers in Nutrition, 2026)
BackgroundThe increasing demand for natural food preservation methods has drawn attention to lactic acid bacteria (LAB) due to their antimicrobial potential. In this study, two mixed LAB cultures (MCP1 and MCP2), composed of four Lactococcus lactis subsp. cremoris strains isolated from Algerian dromedary camel milk, were evaluated for their biopreservative efficacy in fresh beef stored at 8 °C.MethodsNineteen initial LAB isolates were screened for safety, low-temperature growth, CO₂ production, antibacterial and antioxidant activity, and inter-strain compatibility. Selected strains were identified by MALDI-TOF MS and 16S rRNA sequencing, and their acidifying power was assessed.ResultsMCP2 showed a strong inhibitory effect on total aerobic mesophilic count (TAMC), with a significant 2.66 log₁₀ CFU/g reduction (−24.18%) after six days. Both cultures reduced total coliforms (TC), while MCP1 demonstrated superior antistaphylococcal activity, achieving a 5.55 log₁₀ CFU/g reduction (−50.45%) in Staphylococcus aureus after 10 days. MCP2 achieved a lesser reduction of 1.89 log₁₀ CFU/g (−17.18%).ConclusionThese findings highlight the potential of camel-derived LAB as natural protective cultures for meat biopreservation, reducing spoilage and enhancing microbial safety. Further studies should explore their effects on sensory attributes and integration with packaging technologies.